2023
DOI: 10.1128/aem.01863-22
|View full text |Cite
|
Sign up to set email alerts
|

Loosenin-Like Proteins from Phanerochaete carnosa Impact Both Cellulose and Chitin Fiber Networks

Abstract: The present study deepens investigations of microbial expansin-related proteins and their applied significance by (i) reporting a detailed comparison of diverse loosenins encoded by the same organism, (ii) considering both cellulosic and chitin-containing materials as targeted substrates, and (iii) investigating the impact of the C-terminal carbohydrate binding module (CBM) present in other expansin-related proteins on loosenin function. By revealing the potential of fungal loosenins to impact both cellulose a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Study by researchers at the Autonomous University of the State of Morelos, Mexico (Quiroz-Castañeda et al, 2011), which coined the term loosenin, describes a loosenin isolated from the white-rot fungus Bjerkandera adusta with a capability to loosen cotton fibres. A recent study on the substrate binding of loosenins, demonstrated loosenin binding preference for chitin, suggesting a function in fungal cell wall morphogenesis (Monschein et al, 2023). Development of new methods for action mechanism determination would be beneficial in order to study non-hydrolytic proteins, as an absence of activity is a result difficult to publish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Study by researchers at the Autonomous University of the State of Morelos, Mexico (Quiroz-Castañeda et al, 2011), which coined the term loosenin, describes a loosenin isolated from the white-rot fungus Bjerkandera adusta with a capability to loosen cotton fibres. A recent study on the substrate binding of loosenins, demonstrated loosenin binding preference for chitin, suggesting a function in fungal cell wall morphogenesis (Monschein et al, 2023). Development of new methods for action mechanism determination would be beneficial in order to study non-hydrolytic proteins, as an absence of activity is a result difficult to publish.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins were first discovered in Bjerkandera adusta (Quiroz-Castañeda et al, 2011). Loosenins exhibit cellulose fibril loosening behaviour, while it is unclear whether fungi utilize these proteins mainly in pathogenic mechanisms or they serve an analogous function to expansins in plants (Monschein et al, 2023;Quiroz-Castañeda et al, 2011). No structure of loosenins has been experimentally obtained to this date, therefore all structure comparisons rely on homology modelling.…”
Section: Fungal Homologues To Plant Expansinsmentioning
confidence: 99%
See 1 more Smart Citation